A survival guide for restaurant professionals - Gelb, Alan; Levine, Karen (Australia : Thomson Delmar Learning, 2005)
This is a lively, easy-to-read book that is full of anecdotes and useful information for the busy student or professional. With tips from restaurant professionals on everything from organization to stress management to owing your own restaurant, this is one book busy students and professionals won't want to be without.
Chapter 1. Whole Enchilada -- Chapter 2. Taking Inventory -- Chapter 3. Goal Zone -- Chapter 4. Go, Team! -- Chapter 5. Whole You -- Chapter 6. Better Safe Than Sorry -- Chapter 7. Waiting Game -- Chapter 8. More Members of the Team -- Chapter 9. Bring on the Food! -- Chapter 10. Managing Your End -- Chapter 11. Owning It -- Chapter 12. Savvy Professional.
Includes index.
Keywords: FOOD SERVICE